A preclinical study of deep brain stimulation in the ventral tegmental area for alleviating positive psychotic-like behaviors in mice - Lu, Chen; Feng, Yifan; Li, Hongxia; Gao, Zilong; Zhu, Xiaona; Hu, Ji (Frontiers in Human Neuroscience, 2022)
Deep brain stimulation (DBS) is a clinical intervention for the treatment of movement disorders. It has also been applied to the treatment of psychiatric disorders such as depression, anorexia nervosa, obsessive-compulsive disorder, and schizophrenia. Psychiatric disorders including schizophrenia, bipolar disorder, and major depression can lead to psychosis, which can cause patients to lose touch with reality. The ventral tegmental area (VTA), located near the midline of the midbrain, is an important region involved in psychosis. However, the clinical application of electrical stimulation of the VTA to treat psychotic diseases has been limited, and related mechanisms have not been thoroughly studied. In the present study, we attempted to treat positive psychotic-like behaviors by electrically stimulating the VTA in mice and explore the neural mechanisms behind behavioral effects. Local field potential recording and in vivo fiber photometry to observe the behavioral effects and changes in neural activities caused by DBS in the VTA of mice. Optogenetic techniques were used to verify the neural mechanisms underlying the behavioral effects induced by DBS. Our results showed that electrical stimulation of the VTA activates local gamma-aminobutyric acid (GABA) neurons and dopamine (DA) neurons, reduces hyperlocomotion, and relieves stereotyped behaviors induced by MK-801 (dizocilpine) injection. The results of optogenetic manipulation showed that the activation of the VTA GABA neurons, but not DA neurons, is involved in the alleviation of hyperlocomotion and stereotyped behaviors. We visualized changes in the activity of specific types in specific brain areas induced by DBS, and explored the neural mechanism of DBS in alleviating positive psychotic-like behaviors. This preclinical study not only proposes new technical means of exploring the mechanism of DBS, but also provides experimental justification for the clinical treatment of psychotic diseases by electrical stimulation of the VTA.